O uso atual do solo e da água na bacia do ribeirão Piçarrão-Araguari-MG-Brasil - Elizabete Oliveira Melo; Manfred Fehr (Investigaciones Geográficas, 2010)
The agricultural expansion in the basin of the creek Piçarrão during the period from 1970 to 2005 produced changes in the use of soil and water that heretofore had not been documented. A diagnosis of the present situation was carried out to evaluate the prospect of agricultural activity in the basin. The literature was reviewed, 16 rural producers were interviewed, and the creek and its tributaries were inspected. The results of the study are presented in form of maps and tables. The total area drained by the creek is 388 km², nine pivots do the agricultural irrigation, and the creek's flow rate varies between 1.5 and 80.0 m³ per second with an annual average of 8.0 m³ per second. The study identified water availability as main limiting factor of agricultural development in the basin.